Abnormal keratin expression pattern in prurigo nodularis epidermis. Issue 1 (1st December 2021) - Yang, L. L.; Jiang, B.; Chen, S. H.; Liu, H. Y.; Chen, T. T.; Huang, L. H.; Yang, M.; Ding, J.; He, J. J.; Li, J. J.; Yu, B.
Abstract: Background: Prurigo nodularis (PN) is a highly pruritic, chronic dermatosis and difficult to treat. PN lesions are characterized by existence of many hyperkeratotic, erosive papules and nodules. However, the pathogenesis of PN still remains unelucidated. Aim: To clarify the keratin role in the epidermis hyperproliferation, the keratin expression pattern in the PN lesional skin. Methods: In this study, we enrolled 24 patients with PN and 9 healthy control volunteers. K1/K10, K5/K14, K6/K16/K17 expression pattern were investigated by using immunohistochemical staining. Results: The lesional skin consists of the thickened spinous layers, in which active cell division was found. K5/K14 were upregulated in PN lesional epidermis, the staining signal localized in the basal layer and lower suprabasal layers. Hyperproliferation‐associated K6 was found in all layers of epidermal lesional skin, especially in the spinous layers. In contrast, K16 was only detected in the basal and lower suprabasal layers, K17 was observed in the basal and spinous layers. Terminal differential keratins K1/K10 were upregulated, detected in the pan‐epidermis, but spared in the basal and low suprabasal layers. Conclusion: The keratinocytes enter an alternative differentiation pathway, which are responsible for the activated keratinocyte phenotype, abnormal keratins expression potentially contributes to the keratinocytes proliferation, subsequently lead to increased lesional skin epidermis thickness, hyperkeratiosis and alteration of skin barrier properties. Abstract : Figure 1. Keratins expression pattern in PN lesional skin epidermis